Prevalence and associated factors of true hypertension among primary school children in the Klang Valley: A cross - sectional study - Devaraj, Navin Kumar; Saeed Ghaloo, Sobia; Ponnudurai, Regan Fu; Kamalan, Vanessa Rohini; Ling, Ying Wong; Kaneson, Vishalini; Abdul Halim, Suriani Akbar (University of Malta, 2023)
Introduction: Hypertension is an important risk factor for cardiovascular disease and there is an increasing risk of development of hypertension among children. Our study aims to determine the prevalence of true hypertension and its associated factors among primary school children in the Klang Valley region. Methods: A self-administered questionnaire was used which explores the socio-demographic background, past medical history, family history & lifestyle characteristics of the participants. Diagnosis of hypertension were based on standard protocol. Data analysis was done using SPSS v26.0. Results: This study involved 251 respondents. The prevalence of true hypertension among primary school children is 2. Significant determinant of true hypertension were higher body mass index (BMI), children living with single parent and being of Indian ethnicity. It was found that Indians had 55 times higher odds of having true hypertension compared to Malays (95CI =1.47-2061.87, p = 0.03). It was also found that children from households with a single parent had 85 times higher odds of having true hypertension compared to households with both parents (95CI = 2.68-2537.53, p = 0.01). In addition, those with a higher BMI had 1.4 times higher odds of having true hypertension (95CI = 1.06-1.43, p = 0.018). Conclusion: The prevalence of true hypertension is similar to the rates reported globally. This provides an insight where regular BP monitoring in children should be advocated amongst healthcare professionals, especially amongst children having risk factors for the development of hypertension.